One-Session Treatment of a Specific Phobia of Swallowing Pills: A Case Study. (December 2013) - Davis, Thompson E.; Reuther, Erin T.; Rudy, Brittany M.
This case study presents the treatment of a 23-year-old single White male with a specific phobia of swallowing and choking on pills. He presented for treatment as part of a larger treatment study for specific phobia and met criteria for a specific phobia, other type (swallowing pills), and social phobia. Treatment of the specific phobia involved One-Session Treatment and was conducted per Zlomke and Davis and Davis, Ollendick, and Öst. A posttreatment assessment 3 weeks after treatment and an 8-week follow-up assessment revealed significant improvements. At both assessments following treatment, clinician severity ratings on the Anxiety Disorders Inverview Schedule—Client (ADIS-IV) decreased, indicating no significant impairment, and the ADIS-IVs at those time periods indicated he no longer met criteria for a specific phobia. Improvements were also seen in the client's self-reported fear, on his ratings of catastrophic cognitions, on a behavioral avoidance task, and in the comorbid social phobia symptoms.